Study of the Relationship Between the Acoustic Threshold and Threshold of Octave Masking - Jagadish A (Journal of All India Institute of Speech and Hearing, 1970)
The value of the test battery approach in assessing human auditory function has been recognized for many years and may prove a more reliable approach to susceptibility testing. If several correlates were identified, they could be used as a  test battery for susceptibility to noise-induced hearing loss. Psycho-acoustic tasks could be used as a new  indices of susceptibility  to  noise-induced  hearing loss, replacing traditional TTS-based susceptibility  tests. The identification of psychoacoustic correlates  of TTS  may also  provide  new  information about th e areas of the  auditory system  involved  in the fatigue process and it  may  also  be useful  in detecting  minimal  auditory  dysfunction. (Eldrege  and  Miller  1969, Ward and Durall  1971,  Lipscomb,  1975).